Political organizations, cults, and ceremonies of the Plains-Ojibway and Plains-Cree Indians. Anthropological papers of the AMNH - Skinner, Alanson, 1886-1925. (New York : Published by order of the Trustees [of the American Museum of Natural History], 1914)
1. p. l., p. 475-542. illus. 25 cm.